1990
DOI: 10.1016/0014-5793(90)80053-l
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quercetin on cell cycle progression and growth of human gastric cancer cells

Abstract: Quercetin, a flavonoid, is found in many plants, including edible fruits and vegetables. We examined the effects on cell growth of human malignant cells derived from the gastrointestinal tract and on cell cycle progression. Quercetin markedly inhibited the growth of human gastric cancer cells and the ICsO value was 32-55 PM. DNA synthesis was suppressed to 14% of the control level by the treatment with 70 PM quercetin for 2 days.Furthermore, quercetin blocked cell progression from the Gi to the S phase.Quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
0
7

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(148 citation statements)
references
References 15 publications
8
132
0
7
Order By: Relevance
“…This observation is in agreement with previous studies on human gastric cancer (Yoshida et al, 1990) and IM 9 lymphoblastoid cells (unpublished observation). Interestingly, primary ovarian tumours express appreciable amounts of type II EBS.…”
Section: Nm)supporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in agreement with previous studies on human gastric cancer (Yoshida et al, 1990) and IM 9 lymphoblastoid cells (unpublished observation). Interestingly, primary ovarian tumours express appreciable amounts of type II EBS.…”
Section: Nm)supporting
confidence: 94%
“…Our data indicate that the flavonoid Q inhibits the growth of human ovarian cancer cells. This finding is in agreement with previous studies showing that Q has an antiproliferative action against human cancer cells in vitro (Markaverich et al, 1988;Yoshida et al, 1990). The observation that a dietary supplement of Q inhibits the development of 7,12-dimethylbenzanthracene and N-nitrosomethylurea induced rat mammary cancer (Verma et al, 1988) strongly support the possibility that Q could also be active in vivo.…”
Section: Nm)supporting
confidence: 92%
“…38 Consistent with previous reports, our study showed that quercetin inhibited proliferation and induced apoptosis in gastric cancer cells. 9 Autophagy is an evolutionary conserved, dynamic and lysosome-mediated process that involves the sequestration and delivery of cytoplasmic material to the lysosome where it is degraded and recycled. 39,40 Accumulating anticancer agents have been documented to trigger the cellular autophagic process, but the role that autophagy plays in cancer chemotherapy is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…attracted much attention in relation to its anticancer activities in many cancer cell models, including lymphoma, ovary, endometrial, prostate, liver and gastric cancer; [6][7][8][9] however, the molecular mechanisms underlying quercetin-mediated cellular responses remain poorly defined.…”
Section: Quercetin Induces Protective Autophagy In Gastric Cancer Cellsmentioning
confidence: 99%
“…Urinary phyto-oestrogen levels are also decreased in women with breast cancer (Ingram et al, 1997). Soyabean diets and individual isoflavones have also been shown to offer protection against mammary tumour development in animal models of cancer (Troll et al, 1980;Lamartiniere et al, 1995) and the related, naturally occurring flavone, quercetin, has been shown to decrease the growth of gastric cancer cells (Yoshida et al, 1990). It is likely that several anticancer mechanisms are involved in the protection offered by dietary isoflavones, examples that we have shown here are that apoptosis, oestrogenicity and tyrosine kinase inhibition may play a role.…”
Section: Discussionmentioning
confidence: 99%